Biodegradable nanoparticle-entrapped vaccine induces cross-protective immune response against a virulent heterologous respiratory viral infection in pigs. - Varun Dwivedi (PLoS ONE, 2012)
Biodegradable nanoparticle-based vaccine development research is unexplored in large animals and humans. In this study, we illustrated the efficacy of nanoparticle-entrapped UV-killed virus vaccine against an economically important respiratory viral disease of pigs called porcine reproductive and respiratory syndrome virus (PRRSV). We entrapped PLGA [poly (lactide-co-glycolides)] nanoparticles with killed PRRSV antigens (Nano-KAg) and detected its phagocytosis by pig alveolar macrophages. Single doses of Nano-KAg vaccine administered intranasally to pigs upregulated innate and PRRSV specific adaptive responses. In a virulent heterologous PRRSV challenge study, Nano-KAg vaccine significantly reduced the lung pathology and viremia, and the viral load in the lungs. Immunologically, enhanced innate and adaptive immune cell population and associated cytokines with decreased secretion of immunosuppressive mediators were observed at both mucosal sites and blood. In summary, we demonstrated the benefits of intranasal delivery of nanoparticle-based viral vaccine in eliciting cross-protective immune response in pigs, a potential large animal model.